The evolution of the technical and economic indicators for crop rice in Romania period 2006-2016 - Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Romania has been particularly interested in rice culture since the 1930s through culture and biology technology, which has made it possible to capitalize less productive land productivity on other crops. In the present study we will analyze the technical indicators of the cultivated area and the production averages, as well as the economic indicators represented by the prices, the subsidies granted / ha an the trade balance. The research method used will be the quantitative and qualitative analysis of the statistical data series from 2006 to 2016. The aim of the study is to highlight the technical and economic aspects of the studied culture, their dynamics and the importance of rice culture that reflects on the demand of the national market.
Keywords: Q10; Q11; Q18; 330; indicators; areas; average output; price